Strategi Kepemimpinan Kepala Sekolah dalam Manajemen Konflik di Lingkungan Pendidikan - Rohaini, Amira; Fathoni, Tamrin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study explores the leadership strategies of school principals in managing conflicts within educational environments. Using a library research method, this study analyzes effective conflict management strategies, including communication, mediation, collaboration, empowerment, and regular evaluations. The results highlight that these strategies are crucial in fostering a harmonious school climate, reducing tensions, and preventing future conflicts. The findings emphasize that proactive, inclusive leadership significantly contributes to a positive educational setting